ESTABLISHMENT AND CHARACTERIZATION OF ETHIDIUM BROMIDE RESISTANCE IN SIMIAN VIRUS 40-TRANSFORMED HAMSTER CELLS : Effects on Mitochondria In Vivo - Klietmann, Wolfgang (The Rockefeller University Press, 1973)
This study describes the isolation and subsequent characterization of four mammalian cell lines resistant to ethidium bromide (EB). Treatment of the simian virus 40- (SV40) transformed hamster cell line F5-1 first led to the establishment of the F2 cell line, which is resistant to 2 µg EB/ml. At this concentration cytochromes c and b are present in almost normal or only slightly diminished amounts, whereas cytochromes a + a (3) show an obvious decrease. The mitochondria of the F2 cell show a normal ultrastructure, not distinct from the parental cell line F5-1, and contain closed circular DNA. The sensitive parental F5-1 cells, however, when exposed to the same dye concentration exhibit the typical EB-induced ultrastructural changes in the mitochondria, and no more component I mitochondrial DNA can be demonstrated. 1 yr after establishment we derived from the F2 cell three more cell lines, resistant against 4, 8, and 16 µg of EB/ml. These cell lines, termed F4, F8, and F16, respectively, also revealed relatively intact-appearing mitochondria, although distinguishable from F5-1 and F2 mitochondria by a more condensed or unorthodox cristae conformation. F4, F8, and F16 cell lines contained closed circular mitochondrial DNA in the same position as that of the parental F5-1 cells, when analyzed in an isopycnic CsCl-EB gradient. A small shoulder at the lower density side of the DNA I peaks was observed. The newly acquired drug resistance of the F cells is hereditarily transmitted to the progeny cells and retained even after a period of growth in EB-free medium.